PEMODELAN PENGINDERAAN JAUH UNTUK ESTIMASI SIMPANAN KARBON DI BLOK 1 PT ALAM BUKIT TIGAPULUH - Arief Firmansyah; Hamzah Hamzah; Eva Achmad (Journal of Science and Applicative Technology, 2022)
Biomass calculations are useful for knowing the amount of carbon stored in a forest ecosystem and essential steps to mitigate global warming and climate change. Restoration activities at PT Alam Bukit Tigapuluh (PT ABT) have indirectly made efforts to absorb carbon dioxide (CO2). This study aimed to analyze and measure carbon storage as well a model and map carbon storage at PT ABT. The method used the survey method of species, diameter at breast height, and vegetation height with a plot size of 20mx20m. The research conducted to analyze carbon storage and build a regression model. The results showed that the average carbon storage of the 30 plots was 259.32 tons/ha and the estimated carbon storage is 5,496,233 tC. The best regression model’s modelling result are Y = -817 + 331.5 MSRVI with the correlation of determination being 76.40%. The distribution of carbon storage in PT ABT is divided into 5 classes, namely, non-vegetated class (<0 tons/ha) of 57 ha, low (0-112.55 tons/ha) of 291 ha, medium (112.55-225.11 tons/ha) covering an area of ​​2,059 ha, high (225.11-337.67 tons/ha) covering an area of ​​18,533 ha and very high (>337.67 tons/ha) covering an area of ​​1,256 ha.